THE RELATIONSHIP OF SELF EFFICACY AND NURSE'S WORK STRESS IN THE ICU - Renny Triwijayanti; Sandika Sandika; Romiko Romiko; Feby Puryanti ((IJP) Indonesia Jurnal Perawat, 2022)
AbstrakThe highest prevalence of work stress in health workers is experienced by nurses. So that stress can be eliminated properly, this is called self-efficacy . This study aims to determine the relationship between self -efficacy and work stress of nurses in the Inpatient Room. This type of research is a quantitative research with an analytical descriptive research design and uses a cross sectional approach . Samples were taken with a total sampling technique of 48 nurses. Analysis using chi square . The results showed that of the 29 nurses who had high self-efficacy there were 21 respondents (72.4%) who did not experience work stress and 8 respondents who had high self-efficacy experienced work stress. Meanwhile, from 19 nurses who had low self-efficacy , there were 12 respondents (63.2%) who experienced work stress and 7 respondents who had low self-efficacy did not have work stress. There is a relationship between self-efficacy and work stress of nurses. Obtained p Value = 0.032 ( p Value 0.05).  it is expected for hospitals to increase self-efficacy by conducting training on positive thinking and forming guidance groups with modeling techniques. And to prevent work stress through exercise, personal refreshing, relaxation techniques and outbound . As well as an evaluation by the hospital management in every nursing action given by the patient.